The Effectiveness of Cassava Peel (Manihot esculenta crantz) in Reducing Iron (Fe) Levels in Dug Well Water - Alfina, Melly; Khair, Abdul; Hamzani, Sulaiman; Juanda, Juanda (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
This results in unsuitable water quality. A natural ingredient can be used to treat wastewater from cassava peel. This study aimed to ascertain the variation in iron (Fe) levels in dug well water before and after cassava peel treatment. This pure experimental research used a posttest-only control group design method. The research population consisted of water from a dug well in Sungai Tiung Village, Banjarbaru City, which contains high iron levels. The research sample was part of the dug-well water. The Kruskal-Wallis statistical test revealed a significant difference between treatments, prompting using the Mann-Whitney test. Further statistical tests yielded the asymptote value Sig. (2-tailed) < 0.05, indicating significant differences between doses of 0 grams and 1 gram, 1.5 grams, 2 grams, 2.5 grams, and 3 grams; the dose of 1 gram and 2.5 grams and 3 grams; and the dose of 1.5 grams and 2.5 grams and 3 grams. The study concluded that using cassava peel for water treatment effectively reduces iron content. Further research is recommended to achieve iron levels by quality standards by varying the time of the coagulation-flocculation process and conducting a preliminary test to determine the optimal dose variation.